The influence of relaxation with electromyography and Islamic prayer programs for female Muslim - Jing, Wang; Abdul Wahab, Muhanmad Nubli; Abdalla, Ahmad N; Gu, Ming; Liu, Yao; Mohd Noor, Hanisah (Academic Journals, 2012)
Chronic work-related stress can fray nerves, keep you up at night and contribute to significant and independent risk problems such as heart disease and depression. Particularly, chronic job strain can put both your physical and emotional health at risk. Muscle relaxation is a useful evidence based teaching and treatment approach for physical/remedial therapists. It can show unnecessary covert muscles co-contractions and the muscles staying tense after performing a task and not relaxing. The physiological monitoring can identify low level muscle activity which is not recognized by either the client or the therapist. Electromyography (EMG) allows the invisible muscle tension to become visible and is illustrated through a case study of a client who sought treatment because of shoulder pain. Her pain started when she became employed in a vegetable store and continued to increase to the point that she was afraid that she would have to stop working. During the assessment sessions, the trapezius and deltoid EMG were recorded while her role played her job task which is keyboard typewriting practice programs. The EMG showed increased shoulder tension, which did not return to baseline; there baseline was also an absence of regenerative EMG gaps. Salah is the physically demanding practice of formal prayer in Islam that helps adjust the rhythm of the body. After Salah training for clients, substantial upper trapezius muscles activity can be demonstrated. In the present investigation, the muscle activity of the right and left external upper trapezius muscles was examined to assess the level of muscle activity during Islamic prayer. The EMG showed more significant decrease and relaxation compared with non-training tasks of clients. After actually training using Salah with reduced dysponesis, the client reported a significant decrease in headache and less exhaustion after a day’s work. At 1 month follow up, she reported a significant decrease in her shoulder complaints and was able to continue her job without shoulder problems. In summary, the findings are EMG-based. Salah augments the behavioral interventions because it helps develop internal awareness and enhance health status and reduce the risk of shoulder problems.